Intelligent Sustainability: Harnessing AI for a Greener Future - Sameer Khan; Muhammad Zunnurain Hussain; Muhammad Zulkifl Hasan (Dialogue Social Science Review (DSSR), 2025)
One of the key areas where Artificial Intelligence (AI) can counteract the forces of destruction and promote sustainability is intelligent decision-making, resource allocation, and minimizing environmental impact. This paper focuses on how AI aids environmental surveillance, energy management, waste management, and sustainable agriculture. AI-powered systems enhance climate modeling, energy grid optimization, supply chain efficiency, and recycling processes. By utilizing large datasets, real-time analytics, and AI, intelligent automation supports sustainability efforts globally. However, ethical concerns and energy consumption challenges should not deter AI from becoming a driving force in a greener future, especially with emerging technologies like blockchain and IoT. The objective of this paper is to explore AI's role in sustainable development through its applications, challenges, and future directions, demonstrating how AI-driven solutions can create a more resilient and environmentally friendly world.